An Evaluation of Binocular and Accommodative Function as Predictors of Myopia Progression - Hatch, Stanley (Canadian Journal of Optometry, 2025)
Abstract Introduction This study was designed to evaluate whether common tests of binocular and accommodative function can predict myopia progression in children. The study explored lesser-studied clinical measures beyond accommodative lag and phoria. Methods This retrospective cohort study reviewed patients from age 5 years 0 months up to but not including the 17th birthday in an urban academic U.S. clinic. We measured binocular and accommodative functions in a sample of 410 patients with normal corrected visual acuity. The functions were correlated to change in cycloplegic refraction over time. Results The mean observation period was 2.59 ± 0.70 years. Pearson’s correlation coefficients between binocular/accommodative measures and refractive change were weak (r = -0.02 to 0.03). Excluding patients with constant strabismus and stratifying by phoria type (exodeviation or esodeviation), along with fusional vergence metrics, failed to make any meaningful improvements (r = -0.10 to 0.07). Even among patients at high-risk for myopia and myopia progression (baseline refraction ≤ 0.75D), correlations remained weak (r = -0.12 to 0.06). Conclusion In this clinic sample, common tests of binocular vision and accommodation were independent of change in refractive error and did not discriminate future myopia conversion or progression.